Out-of-Africa migration and Neolithic coexpansion of Mycobacterium tuberculosis with modern humans. - Comas, I; Comas, I; Coscolla, M; Luo, T; Borrell, S; Holt, K; Kato-Maeda, M; Parkhill, J; Parkhill, J; Malla, B; Berg, S; Thwaites, G; et al. (2013)
Tuberculosis caused 20% of all human deaths in the Western world between the seventeenth and nineteenth centuries and remains a cause of high mortality in developing countries. In analogy to other crowd diseases, the origin of human tuberculosis has been associated with the Neolithic Demographic Transition, but recent studies point to a much earlier origin. We analyzed the whole genomes of 259 M. tuberculosis complex (MTBC) strains and used this data set to characterize global diversity and to reconstruct the evolutionary history of this pathogen. Coalescent analyses indicate that MTBC emerged about 70,000 years ago, accompanied migrations of anatomically modern humans out of Africa and expanded as a consequence of increases in human population density during the Neolithic period. This long coevolutionary history is consistent with MTBC displaying characteristics indicative of adaptation to both low and high host densities.